Characteristics and outcomes of patients with COVID-19 in Hainan, South China. Issue 11 (19th March 2021) - Zheng, Yamei; Gao, Yunsuo; Wu, Biao; Huang, Linhui; Chen, Yongxing; Cai, Xingjun
Abstract : Abstract: As an international tourist center, Hainan province includes both imported and local COVID-19 cases. This study aimed to investigate the clinical characteristics and outcomes of COVID-19 patients in Hainan, China. COVID-19 patients hospitalized in Hainan affiliated Hospital of Hainan Medical University in January to March 2020 were retrospectively assessed. Routine blood tests, blood gas analyses, and computed tomography imaging were performed within 24 hours. Virus nucleic acid was detected every other day. The patients were divided into local resident and traveler groups, and differences in clinical data as well as leukocyte, lymphocyte, and neutrophil levels were analyzed. A total of 70 patients aged 51.23 ± 13.54 years were assessed, including 16 local residents and 54 travelers. Of these, 55 cases (78.6%) had fever, 47 (67.1%) had cough and sputum, and 9 (12.9%) had chest dyspnea; 60 and 10 cases were mild/common and severe/critical, respectively. Sex, basic diseases, smoking history and drinking history, Charlson Comorbidity Index, symptoms, time of onset to admission, clinical severity, white blood cell count, lymphocyte count, neutrophil count, oxygen inhalation, mechanical ventilation, glucocorticoid therapy, treatment, admission to ICU, hospital stay, and mortality were similar between the 2 groups. The warm and humid climate of Hainan does not seem to significantly affect patient features and outcomes from COVID-19. Unnecessary travel to tourist areas should be avoided.